From Hal 9000 to neo-Luddism. Who’s Afraid of Technology? Reflections on the Category of Experience - Joanna Szczepanik (Acta Universitatis Lodziensis: Folia Philosophica, 2025)
The article analyzes the phenomenon of technological anxiety, which is an inseparable element of the 4th Industrial Revolution, and its reverse. At the level of the individual, technological challenges open up, intensified by the excess of stimuli caused by information overload. In this context, the concept of the 4th Industrial Revolution proposed in 2016 by Klaus Schwab is juxtaposed with theoretical proposals such as Neil Postman’s “Technopol”, the reflections of James Ellul, or the radical manifesto of eco-terrorist Ted Kaczyński, concerning the future of industrial society. The article also attempts to define and indicate the sources of technological anxiety, from the feeling of uncertainty, dependence, exclusion, to the loss of control over the world and man himself. The frame is a reference to the text of culture in the form of the figure of the Hal 9000 computer from Stanley Kubrick’s film as a machine making decisions about human life and to the contemporary phenomenon of neo-Luddism inspired by the 19th movement of opponents of the development of technology. Methodologically, the article is based on the subject's literature and the analysis of popular culture texts. It also uses exemplification from the area of contemporary art, reaching for the category of artistic research.